Plastic-less equipment for sampling marine microplastics - Todd, Peter A.; Yong, Clara Lei Xin; Foo, Sze Hui; Ying, Lynette Shu Min; Ledet, Janine (Frontiers in Marine Science, 2024)
Marine microplastics have become a pernicious global pollution issue. As field surveys to determine microplastic abundance in the marine environment and/or biota become more common, it is important to refine collection techniques to minimize contamination of samples. However, most contemporary sampling equipment is fabricated with plastic components. Microplastic contamination during sample collection can be minimized from the onset by employing techniques that are plastic-less or with minimal plastic-to-sample contact. Here we describe plastic-less equipment and techniques for field sampling of water, sediment, and organisms. Some of these are traditional designs that pre-date the plastic era and can be revived or repurposed for microplastic sampling. Others are self-developed and fabricated using materials such as metal, wood, silk, and cork. For relatively small costs in time and funds, it is possible to greatly reduce, or eliminate, plastics from the field sampling process.